FEEDING STIMULATORY EFFECTS OF CYPERUS ROTUND US TUBER ON CIRRHINUS MRIGALA - Venkateshwarlu, G.; Rambabu, M.; Patro, B.; Pal, A. K. (Journal of Indian Fisheries Association, 2015)
Traditionally tubers of cyperus (Cyperus rotundus) and its extracts have been used for alluring fish during harvesting in India. An experiment was conducted to evaluate its feeding stimulatory activity and effect on the growth of a commercially important freshwater fish, Cirrhinus mrigala. Three isonitrogenous and isocaloric formulated diets viz. plant ingredient based control and control supplemented with cyperus tuber (CS) at 1% and 5% levels were fed to the fingerlings of mrigal, Cirrhinus mrigala (2.68 + 0.20 g) for a period of 45 days. Th grq,wth performance and the activity of metabolic enzymes, aspartate aminotransferase (AST) and alanine aminotransferase (ALT), in liver, gill and muscle tissues of mrigal were stu!Hed during- every 15 days interval. Highest relative growth (72.28%) was obtained in the mrigal fed with the diet containing 5% cyperus (5% CS), while the re!z ti" e growths were 66.18% and 43.40% for the fish fed with the 1% CS diet and control respectively. The activities of AST and AL T were significantly higher (p<O.Ol) in both 1% and 5% CS diets as compared to the control in all the tissues studied. Higher aminotransferase activities were observed in the tissues of 5% CS group than in those of 1% CS group throughout the experimental period. The observed higher enzymatic activity was concomitant with the higher growth rate in fish. The results suggested that cyperus tuber supplementation increased feed palatability and growth. Key words: Feeding stimulants, Cyperus rotundus, Cirrhinus mrigala, Aspartate aminotransferase, Alanine aminotransferase